Endoscopic plantar fasciotomy in the treatment of chronic heel pain - Urovitz, Edwin P. (Canadian Medical Association, 2008)
OBJECTIVE: To evaluate endoscopic plantar fasciotomy for the treatment of recalcitrant heel pain. METHOD: We undertook a retrospective study of the use of endoscopic plantar fasciotomy in the treatment of chronic heel pain that was unresponsive to conservative treatment. Over a 10-year period, we reviewed the charts of 55 patients with a minimum 12-month history of heel pain that failed to respond to standard nonoperative methods and had undergone the procedure described. All patients were clinically reviewed and completed a questionnaire based on the American Orthopaedic Foot and Ankle Society (AOFAS) score for ankle and hindfoot. RESULTS: The mean follow-up was 18 months. The mean preoperative AOFAS score was 66.5; the mean postoperative AOFAS score was 88.2. The mean preoperative pain score was 18.6; the mean postoperative pain score was 31.1. Complications were minimal (2 superficial wound infections). Overall, results were favourable in over 80% of patients. CONCLUSION: We conclude that endoscopic plantar fasciotomy is a reasonable option in the treatment of chronic heel pain that fails to respond to a trial of conservative treatment.